PENGARUH KEDISPLINAN, GAYA BELAJAR, KEMANDIRIAN BELAJAR, POLA ASUH ORANG TUA, DAN LINGKUNGAN SEKOLAH TERHADAP MOTIVASI BELAJAR SISWA PELAJARAN EKONOMI - Latifah, Siti; Ronald, Jimi; stevani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research aims to analyze the influence of discipline, learning style, learning independence, parenting patterns, and the school environment on the learning motivation of class X students in Economics subjects at SMAN 1 Siberut Selatan. The research uses a quantitative approach with survey methods. The research population was 232 students, and 147 students were selected as samples using probability sampling techniques. The instrument used was a closed questionnaire, while the data analysis technique was carried out through path analysis with the t test, F test, and multilevel test. The research results show that learning style, learning independence, parenting patterns, and the school environment have a significant effect on discipline. Discipline is proven to have a significant effect on learning motivation, while learning style, learning independence, and parenting patterns also have a significant effect on learning motivation. However, the school environment does not have a significant influence on learning motivation. These findings confirm that both internal and external factors play a role in influencing students' learning motivation, with discipline as an important mediating variable in increasing learning motivation.